Utopie literackie źródłem wiedzy o książce - Dróżdż, Andrzej (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2003)
[Literary Utopias as a Source of Knowledge about Books] For many years literary utopias have raised interest among sociologists, psychologists and historians of literature. They can also be a very valuable source of information about books and libraries. Such an assumption adds another field of research to bibliology; metho-dological techniques gain new possibilities and interpretative concepts widening our scope of knowledge about books. Utopias are deeply rooted in social myths, that is why the author of the present paper first tries to define the myth of the book connected with the myth of the reason. Utopian images of books can manifest themselves in the functioning of both: the book’s external and internal strata. The perspective adopted by the author helps in understanding of the anthropological meaning of the book in the wide cultural context